Australia, Canadá y la IPA nos ofrecen benchmarking en préstamo digital en bibliotecas públicas - Fenoll, Carme (Anuario ThinkEPI, 2015)
Reseñas de los informes: De-Castell, ChristinaÂ (2014).Â Ebooks in 2014: access and licensing at Canadian public libraries.Â Canadian Urban Libraries Council / Conseil desÂ Bibliothí¨ques Urbaines du Canada, April. 18 pp. http://goo.gl/NdsSDo Â Mount, DanÂ (2014).Â Elending landscape report 2014. Canberra: Australian Library and InformationÂ Association, April. 38 pp. http://goo.gl/Ps3XtA Â Thomson, DougalÂ (2014).Â Innovation in e-book lending: new IPA report, 10 pp. http://goo.gl/NxJSmJ